EU drug markets report: in-depth analysis : 2016 (Publications Office of the European Union, 2016)
The EU Drug Markets Report 2016 is the second comprehensive overview of illicit drug markets in the European Union by the EMCDDA and Europol. The analysis presented in this report spans numerous topics such as the links between drugs and other crimes, the licit economy and society more generally as well as the processes and players involved in the trade from production and trafficking to distribution. Taking an evidence-based approach, the report reviews the markets for heroin, cocaine, cannabis, amphetamine, methamphetamine, MDMA and new psychoactive substances. It also provides concrete action points to inform policy development at EU and national level. This report explores the concept of the illicit drug market within the broader context of changing patterns of drug use, cultural and social factors and links to wider criminality. Drug markets continue to be one of the most profitable areas for organised crime groups (OCGs) and it is estimated that EU citizens spend over EUR 24 billion (range EUR 21 to 31 billion) every year on illicit drugs. The impacts that drug markets have on society are correspondingly large and go beyond the harms caused by drug use. They include involvement in other types of criminal activities and in terrorism; impacts on legal businesses and the wider economy; strain on and corruption of government institutions; and impacts on wider society.